No association of maternal gestational weight gain with offspring blood pressure and hypertension at age 18 years in male sibling-pairs: a prospective register-based cohort study. - Elina Scheers Andersson; Per Tynelius; Ellen Aagaard Nohr; Thorkild I A Sørensen; Finn Rasmussen (PLoS ONE)
Background Maternal gestational weight gain (GWG) is associated with birth weight, obesity, and possibly blood pressure (BP) and hypertension in the offspring. These associations may however be confounded by genetic and/or shared environmental factors. In contrast to previous studies based on non-siblings and self-reported data, we investigated whether GWG is associated with offspring BP and hypertension, in a register-based cohort of full brothers while controlling for fixed shared effects. Methods By using Swedish nation-wide record-linkage data, we identified women with at least two male children (full brothers) born 1982-1989. Their BP was obtained from the mandatory military conscription induction tests. We adopted linear and Poisson regression models with robust variance, using generalized estimating equations to analyze associations between GWG and BP, as well as with hypertension, within and between offspring sibling-pairs. Results Complete data on the mothers' GWG and offspring BP was obtained for 9,816 brothers (4,908 brother-pairs). Adjusted regression models showed no significant associations between GWG and SBP (β = 0.03 mmHg per 1-kg GWG difference, [95% CI -0.08, 0.14], or DBP (β = -0.03 mmHg per 1-kg GWG difference [95% CI -0.11, 0.05]), or between GWG and offspring's risk of hypertension (relative risk = 1.0 [95% CI 0.99, 1.02], neither within nor between siblings. Conclusions In this large sibling-pair study, we did not find any significant association between GWG and offspring BP or the risk of hypertension at 18y, when taking genetic and environmental factors shared within sibling pairs into account. Further large sibling studies are required to confirm a null association between GWG and other cardiovascular risk factors.